2005
DOI: 10.1109/tmi.2004.842453
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated penalized weighted least-squares and maximum likelihood algorithms for reconstructing transmission images from PET transmission data

Abstract: We present penalized weighted least-squares (PWLS) and penalized maximum-likelihood (PML) methods for reconstructing transmission images from positron emission tomography transmission data. First, we view the problem of minimizing the weighted least-squares (WLS) and maximum likelihood objective functions as a sequence of nonnegative least-squares minimization problems. This viewpoint follows from using certain quadratic functions as surrogate functions for the WLS and maximum likelihood objective functions. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…In other words, this algorithm monotonically increases the objective function with increasing iterations. Later, in [24] a de-coupled surrogate function (i.e., no terms of the form , except when ) satisfying (C1) and (C2) was suggested (25) where is a constant and is the number of nonzero elements in the row of . Additional definitions are: and , where the diagonal matrix and vector are defined by (23)- (26) in [24].…”
Section: Cse Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, this algorithm monotonically increases the objective function with increasing iterations. Later, in [24] a de-coupled surrogate function (i.e., no terms of the form , except when ) satisfying (C1) and (C2) was suggested (25) where is a constant and is the number of nonzero elements in the row of . Additional definitions are: and , where the diagonal matrix and vector are defined by (23)- (26) in [24].…”
Section: Cse Algorithmmentioning
confidence: 99%
“…Additional definitions are: and , where the diagonal matrix and vector are defined by (23)- (26) in [24]. For details on (25), see (75) in Appendix B of [24]. The advantage of using the de-coupled surrogate functions is that the updates for the algorithm have closed form solutions and the algorithm is monotonic.…”
Section: Cse Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Iterative image reconstruction methods have attracted considerable attention in the past decades for applications in positron emission tomography (PET) due to the feasibility of incorporating the physical and statistical properties of the imaging process more completely [4,25]. So far, all statistical reconstruction algorithms are based on the maximum likelihood (ML) or the least squares cost function.…”
Section: Introductionmentioning
confidence: 99%
“…Another class of iterative image reconstruction methods made use of the weighted least squares (WLS) method [4,13]. Recently, Anderson et al [4] developed a WLS algorithm and demonstrated that this algorithm converged faster than the ML-EM and produced images that were significantly of better resolution and contrast.…”
Section: Introductionmentioning
confidence: 99%